Increased Frequency of CTLA-4 and PD-1 Expressing Regulatory T Cells and Basophils With an Activating Profile in Infants With Moderate-to-Severe Atopic Dermatitis Hypersensitized to Food Allergens - Bilbao, Agurtzane; Pérez-Garay, Raquel; Rius, Idoia; Irurzun, Alex; Terrén, Iñigo; Orrantia, Ane; Astarloa-Pando, Gabirel; Borrego, Francisco; Zenarruzabeitia, Olatz (Frontiers in Pediatrics, 2021)
Background: Infants with severe atopic dermatitis (AD) may be sensitized to foods that have not been introduced into their diet, posing a risk for developing an immediate hypersensitivity reaction on the first exposure to the food to which they are sensitized. The aim of this work was to perform an analysis of the sensitization profile in infants with moderate-to-severe AD and to identify cellular and molecular markers for food allergy (FA). Methods: Blood samples from healthy donors and children with moderate-to-severe AD were studied. Specific IgE to several allergens were determined using ImmunoCAP FEIA system and ISAC technology. Furthermore, using flow cytometry-based studies, basophils and regulatory T (Treg) cells were phenotypically characterized. Results: 90% of children with AD were sensitized to food antigens before introducing them into the diet, and 100% developed FA. Phenotypic analysis showed a significantly higher percentage of CTLA-4 and PD-1 expressing Treg cells in AD patients than in healthy controls. Basophils from patients exhibited a marked reduction in the expression of CD300a, higher expression of FcεRI and CXCR4, and to some extent higher expression of CD63 and CD300c. Conclusions: Infants with moderate-to-severe AD are at high risk of being sensitized to food allergens. Therefore, to avoid allergic reactions, broad-spectrum sensitization studies are necessary before introducing complementary diet. Increased expression of CTLA-4 and PD-1 suggests greater suppressive potential of Treg cells in infants with AD than healthy controls. Furthermore, our results suggest a role for CD300 molecules on circulating basophils as possible biomarkers for FA susceptibility.